Analysis of the effectiveness of methods for ensuring the reliability of a communication satellite transponder - T. E. Gelfman; A. P. Pirkhavka; V. O. Skripachev (Российский технологический журнал, 2023)
Objectives. Since the launch of satellite communication systems in practical use, approaches towards enhancing their operational quality and durability have been developing in the direction of increased reliability of airborne transponders. This is mainly achieved by increasing redundancy and using components with a lower failure rate. In this regard, the creation of new technologies and new materials is a particularly promising direction. However, since durability testing of complex systems can take several years, the problem of ensuring an effective combination of redundancy methods and elements having a reduced failure rate remains challenging. The purpose of the work is to analyze the effectiveness of methods for ensuring the reliability of a communication satellite transponder based on a proposed methodology for determining the durability index using a mathematical model of the probability of failure-free operation.Methods. In order to describe the complex structure of a satellite communication system transponder, a logical- probabilistic method is used, in which the dependence of the system reliability indicators on the reliability indicators of the transponder elements is formulated as a logical function of operability. Mathematical models of system reliability are created on this basis including for redundant systems. Graphs and analytical methods are used to compare different systems.Results. The influence of various methods for ensuring the redundancy of transponder devices and the use of more reliable components on the reliability and durability indicators is considered. A gamma-percentage resource-based technique for determining the durability indicator based on the constructed mathematical models of the probability of failure-free operation is presented along with a comparative analysis of measures to increase the gamma-percentage resource of the transponder.Conclusions. The presented method for determining the durability index using a mathematical model of the probability of no-failure operation can be used to determine the time interval within which redundancy increases the probability of no-failure operation as compared with a decrease in the failure rate of elements. On this basis, the most effective combination of redundancy methods and approaches for reducing the failure rate of elements can be identified.